A USER-ORIENTED CONCEPTUAL FRAMEWORK FOR ELECTRIC BUS ADOPTION IN INDONESIA URBAN PUBLIC TRANSPORT - Resia Atsiila; Wahyudi Sutopo; Yuniaristanto (RADJA PUBLIKA, 2026)
Electric buses are increasingly promoted as a sustainable public transportation solution in Indonesia's urban areas, yet their adoption rate from the user perspective remains relatively limited. This study aims to develop a user-oriented conceptual framework to explain the adoption process of electric bus services within Indonesia's urban public transportation system. The study employs a systematic literature review approach following PRISMA guidelines, analysing scientific articles published from 2015 to 2025, with a total of 30 studies examined in depth. Through content analysis, 13 main constructs were identified that integrate behavioral, psychological, technology acceptance, service attribute, and risk perception dimensions, based on the Technology Acceptance Model and the Theory of Planned Behaviour. Based on this synthesis, this study proposes a process-based conceptual framework that maps the stages of electric bus adoption, from evaluating service attributes to actual usage. To strengthen its empirical applicability, the constructs were operationalized into measurable questionnaire indicators adapted from prior studies and supported through expert review and pilot testing with electric bus users. This framework is positioned as an exploratory model to support the identification of factor structures and serve as a basis for empirical Research and the formulation of sustainable public transportation policies in Indonesia.